Marigold's decision - Giberne, Agnes, 1845-1939; Lance, W. (Salt Lake City, UT : Project Gutenberg, 2024)
"Marigold's Decision" by Agnes Giberne is a novel written in the late 19th century. The story revolves around a young woman named Marigold Plunkett, who navigates the complexities of her family life, particularly with her stepmother, Mrs. Plunkett, and her younger sister, Narcissus. The narrative delves into themes of duty, family loyalty, and the struggle for personal happiness as Marigold contends with her stepmother$1 (Bs ill temper and her own aspirations for a brighter future. The opening of the novel introduces us to the Plunkett household, characterized by a small and disorderly home, where tensions rise due to the dynamics between Marigold, her father Josiah, and her stepmother. Josiah$1 (Bs rough yet loving disposition towards his daughters stands in stark contrast to Mrs. Plunkett's sourness, which affects their family life. As Marigold seeks to bring order and care to her environment, we see her relationship with her father and her burgeoning desire for independence, further complicated by her interactions with James Todd, a local young man who admires her. The chapter sets the stage for Marigold$1 (Bs decision-making journey amidst familial responsibilities and her growing awareness of her heart$1 (Bs desires. (This is an automatically generated summary.)s
Release date is 2024-06-30
Keywords: Christian life -- Juvenile fiction; Conduct of life -- Juvenile fiction; Family -- Juvenile fiction; Siblings -- Juvenile fiction; Temper -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Clergy -- Juvenile fiction; Pride and vanity -- Juvenile fiction; Zoos -- Juvenile fiction